2021
DOI: 10.1007/s10557-021-07182-2
|View full text |Cite
|
Sign up to set email alerts
|

An Original Aspirin-Containing Carbonic Anhydrase 9 Inhibitor Overcomes Hypoxia-Induced Drug Resistance to Enhance the Efficacy of Myocardial Protection

Abstract: Purpose Hypoxic microenvironment plays a vital role in myocardial ischemia injury, generally leading to the resistance of chemotherapeutic drugs. This induces an intriguing study on mechanism exploration and prodrug design to overcome the hypoxia induced drug resistance.Methods In this study, we hypothesized that the overexpression of carbonic anhydrase 9 (CAIX) in myocardial cells is closely related to the drug resistance. Herein, bioinformatics analysis, gene knockdown and overexpression assay certi cated th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is recognized as one of the safe modeling agents for the construction of myocardial ischemia models. 28,30 In the blank group, an equal amount of 0.5% sodium carboxymethyl cellulose was injected. In the medicated groups, starting from the third day of modeling, after ISO injection, the drug was given by intraperitoneal injection and again at an interval of 8 h for 3 consecutive days.…”
Section: Synthesis Of Compounds H1−h9mentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized as one of the safe modeling agents for the construction of myocardial ischemia models. 28,30 In the blank group, an equal amount of 0.5% sodium carboxymethyl cellulose was injected. In the medicated groups, starting from the third day of modeling, after ISO injection, the drug was given by intraperitoneal injection and again at an interval of 8 h for 3 consecutive days.…”
Section: Synthesis Of Compounds H1−h9mentioning
confidence: 99%
“…Because the increased electronegativity promotes binding of the NO moiety in the NO donors with heme iron ions in the active center of cytochrome P450 (Cyt-P450), it can facilitate the catalytic release of NO. 30 Therefore, the adjustment of the electronegativity of the −NO terminal at the NO donors can be made to optimize the NO release as expected. It has been reported that the NO release ratio is dependent on the chemical structure of the donor itself and the chemical environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…N-(5-Sulfamoyl-1,3,4-thiadiazol-2-yl)hept-6-ynamide was prepared according to a literature method. 8 NMR spectra were performed on a Bruker 600 MHz Ultra shield spectrometer (Avance AV-500) and reported as parts per million (ppm) from tetramethylsilane (TMS). The final products were characterized by 1 H and 13 C NMR together with ESI-HRMS.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…4-Nitrobenzyl alcohol, 2,6-bis­(hydroxymethyl)-4-methylphenol, 2-azidoacetic acid, and 4-(2-aminoethyl) benzenesulfonamide as well as indomethacin, naproxen, acetazolamide, and benzsulfamide were commercials. N -(5-Sulfamoyl-1,3,4-thiadiazol-2-yl)­hept-6-ynamide was prepared according to a literature method . NMR spectra were performed on a Bruker 600 MHz Ultra shield spectrometer (Avance AV-500) and reported as parts per million (ppm) from tetramethylsilane (TMS).…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation